KINETIKA TRANSPOR Cu(II) OLEH ZAT PEMBAWA OKSIN DENGAN DAN TANPA ASAM OLEAT MELALUI MEMBRAN CAIR FASA RUAH - Refinel -; Emdeniz - (Universitas Andalas, 2009)
Vol. 2, No. 2ABSTRACT Transport of Cu(II) ions with and without oleat acid additive through bulk liquid membrane has been fullfill the kinetic lows of consecutive irreversible first reaction by oxine as carrier in chloroform membrane. Additions of oleat acid 1.57510–3 M could increase Cu(II) transport affectivity on interface of membrane-source phase and receiving-membrane phase. Transport rate constanta value of Cu(II) ions entrance (k1) 0.0454/minute and the membrane exit rate (k2) 0.0364/minute at 301 K with activation energy 51.471 kJ/mol and without oleat acid rate constanta (k1) 0.0236/minute, (k2) 0.0193/minute with activation energy 55.2499 kJ/mol at the same condition. Keywords : bulk liquid membrane, oxine, oleat acid, copper ions